2004
DOI: 10.1089/clo.2004.6.284
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Somatic Cell Nuclear Transfer for In Vitro Production of Antarctic Minke Whale (Balaenoptera bonaerensis) Embryos

Abstract: The objective of this study was to investigate the developmental ability of the whale embryos with interspecies somatic cell nuclear transfer (SCNT) in comparison with bovine or porcine SCNT embryos and parthenotes. There were no significant differences among the proportions of pseud-pronucleus (PPN) formation of whale SCNT oocytes, intraspecies SCNT oocytes and parethenotes. Furthermore, no significant difference was found in the cleavage rates of whale SCNT embryos between 6-dimethylaminopurin (DMAP) and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Nevertheless, our study confirmed the presence of sei whale DNA in one 6-cell iSCNT embryo, which is considered a desirable phenomenon. In our previous study, the 4-cell stage was the maximum level of development obtained in Antarctic minke whale iSCNT embryos, and the presence of whale DNA was confirmed in samples derived from pooled 2-to 4-cell stage embryos [10]. In the present investigation, the maximum level of development of the whale SCNT (whale-whale) embryos was the 8-cell stage, in which the presence of whale DNA was also confirmed by PCR.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Nevertheless, our study confirmed the presence of sei whale DNA in one 6-cell iSCNT embryo, which is considered a desirable phenomenon. In our previous study, the 4-cell stage was the maximum level of development obtained in Antarctic minke whale iSCNT embryos, and the presence of whale DNA was confirmed in samples derived from pooled 2-to 4-cell stage embryos [10]. In the present investigation, the maximum level of development of the whale SCNT (whale-whale) embryos was the 8-cell stage, in which the presence of whale DNA was also confirmed by PCR.…”
supporting
confidence: 82%
“…56: [131][132][133][134][135][136][137][138][139] 2010) esearch on in vitro maturation (IVM), in vitro fertilization (IVF), somatic cell nuclear transfer (SCNT) and in vitro culture (IVC) of whale embryos will greatly contribute to our basic understanding of whale reproductive physiology, resulting, ideally, in the application of various assisted reproductive technologies (ARTs) to increase the population and aid in management of cetaceans. Several studies on ARTs with respect to IVM [1][2][3][4][5][6], cryopreservation of oocytes [2,5,7], IVF [3,8], intracytoplasmic sperm injection (ICSI) [5,6,9] and interspecies SCNT [10] have been conducted in Common minke (Balaenoptera acutorostrata) and Antarctic minke (B. bonaerensis) whales. Recently, we attempted for the first time to produce embryos of sei (B. borealis) whales by IVF of IVM oocytes in a research based ship [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, we have attempted IVM, IVF/ICSI and IVC in an effort to produce minke whale blastocysts; however, no blastocysts has been obtained to date. Ikumi et al [18] attempted interspecies somatic cell nuclear transfer between Antarctic minke whale donor cells and in vitro matured, enucleated bovine or porcine oocytes, but they were unable to produce any blactosysts although they did obtain 2-and 4-cell cleaved whale embryos. The use of freshly collected oocytes from common minke whales captured during the Kushiro Coast Survey would be advantageous in terms of oocyte quality in comparison with oocytes derived from Antractic minke whales, which must be frozen or vitrified on the Research base ship for transport to the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…So, interspecific SCNT (iSCNT) has been explored to produce cloned offspring, and usually includes interspecific somatic cell nuclear transfer and interspecific pregnancy. In previous research, the oocytes of bovine, sheep, and rabbits have been used for iSCNT, and interspecific reconstructed embryos have been obtained [5][6][7][8][9][10][11][12][13]. Interspecific r e c o n s t r u c t e d e m b r y o s c a n i m p l a n t i n t o interspecific uteri, but only three speices have been successfully cloned by iSCNT [14][15][16].…”
mentioning
confidence: 99%